2014
DOI: 10.1007/s11999-013-3356-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Blocks in Shoulder Arthroplasty: How Do They Influence Complications and Length of Stay?

Abstract: Background Regional anesthesia has proven to be a highly effective technique for pain control after total shoulder arthroplasty. However, concerns have been raised about the safety of upper-extremity nerve blocks, particularly with respect to the incidence of perioperative respiratory and neurologic complications, and little is known about their influence, if any, on length of stay after surgery. Questions/purposes Using a large national cohort, we asked: (1) How frequently are upper-extremity peripheral nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Prior research from years 2007-11, also using similar administrative data, found that 21% of patients had a nerve block for total shoulder arthroplasty surgery. 8 Despite the growth in ultrasound-guided regional anesthesia and the national emphasis on opioid reduction strategies, our data confirm the persistent low utilization (20.9%) of regional anesthesia techniques. Given that our data comes from a large cohort of hospitals and health systems…”
Section: Author Manuscriptmentioning
confidence: 53%
“…Prior research from years 2007-11, also using similar administrative data, found that 21% of patients had a nerve block for total shoulder arthroplasty surgery. 8 Despite the growth in ultrasound-guided regional anesthesia and the national emphasis on opioid reduction strategies, our data confirm the persistent low utilization (20.9%) of regional anesthesia techniques. Given that our data comes from a large cohort of hospitals and health systems…”
Section: Author Manuscriptmentioning
confidence: 53%
“…Interscalene brachial plexus block is arguably the gold standard for adjunctive analgesia for total shoulder arthroplasty. 12,36 Gohl et al 13 reported a pain control regimen that included interscalene block in patients undergoing open shoulder procedures. Their study found that patients who received interscalene block in addition to general anesthesia had lower postoperative pain scores compared with those who did not receive an adjunctive block.…”
Section: Discussionmentioning
confidence: 99%
“…Cohorts were defined based on international classification of diseases, ninth revision (ICD-9) procedure codes for shoulder, total hip, and total knee arthroplasty procedures from 2006 through 2016. Regional anesthesia procedures were defined using Current Procedural Terminology (CPT) codes and ICD-9 codes as previously described 2 3. Associated ultrasound use was identified through billing charges, CPT codes (20604, 20606, 20611, 93355, 76930, 76932, 76936, 76937, 76940, 76941, 76942, 76945, 76946, 76948, 76965, 76998) or ICD-9 procedure codes (88.7, 00.2, 38.97).…”
Section: Methodsmentioning
confidence: 99%